2014
DOI: 10.3390/ma7085920
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanical Characterization of Sustainable Composites Based on Recycled and Stabilized Fly Ash

Abstract: This paper reports the results on the use of an innovative inert, based on stabilized fly ash from municipal solid waste incineration as a filler for polypropylene. The starting material, which contains large quantities of leachable Pb and Zn, was stabilized by means of an innovative process using rice husk ash as a waste silica source, together with other fly ashes, such as coal fly ash and flue gas desulfurization residues. The use of all waste materials to obtain a new filler makes the proposed technology e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…The diffractogram of PP (Figure ) exhibited four characteristic peaks of pure PP at 2θ = 14, 18, 20, and 22°, in agreement with the findings of Besco et al (). PP/PET (Figure ) showed three peaks at 2θ = 22, 27, and 36°, of which the peaks at 27 and 36° corresponded to virgin PET (Demirel et al, ) and 22° corresponded to PP.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The diffractogram of PP (Figure ) exhibited four characteristic peaks of pure PP at 2θ = 14, 18, 20, and 22°, in agreement with the findings of Besco et al (). PP/PET (Figure ) showed three peaks at 2θ = 22, 27, and 36°, of which the peaks at 27 and 36° corresponded to virgin PET (Demirel et al, ) and 22° corresponded to PP.…”
Section: Resultssupporting
confidence: 90%
“…The interplaner spacings (d hkl ) in the crystal structures of PP, PP/PET, and PP/PET/Al laminates were calculated (Table ) from their XRD patterns (Figures ) using Bragg's law as reported by Petrova et al (). The experimental d hkl values were compared with the corresponding values for neat polymer components; for example, data of PP experimental vs PP literature , PP/PET experimental vs. PP literature ‐PET literature , and PP/PET/Al experimental vs. PP literature ‐PET literature ‐Al foil literature (Besco et al, ; Can, Arikan, & Çýnar, ; Demirel, Yara', & Elçiçek, ). The results indicate that there was no significant alteration in d hkl values of PP/PET and PP/PET/Al laminates compared to those of pure PET and Al foil.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the fly ash modified with colloidal mesoporous silica (CMS) showed higher flexural and tensile strengths than silanized fly ash at 10-30% filler contents, indicating that CMS-treated fly ash gave better reinforcing behaviour and interfacial bonding as compared to the silane coupling agents. Studies reported by others (Besco et al, 2014(Besco et al, , 2013) also demonstrated an improvement of both flexural and tensile strengths in polymeric materials with incorporating fly ash treated with colloidal mesoporous silica (CMS) because the surface modification using colloidal mesoporous silica (CMS) would enhance the dispersion of fly ash in the polymer matrix and hence resulted in increase of the mechanical strength of composites. Fig.…”
Section: Effect Of Different Surface Modification Of Fly Ash On Mechamentioning
confidence: 88%
“…There are few reports in the literature (Sreekanth et al, 2009;Satheesh et al, 2013) of incineration ash being used as fillers for polymeric materials with promising results, as the ash is able to integrate with and disperse homogenously into the polymer matrix. However, these reports were mainly focused on the coal fly ash (Ahmaruzzaman, 2010) or a mixture of coal fly ash, flue gas desulfurization (FGD) fly ash and MSWI fly ash (Besco et al, 2013(Besco et al, , 2014. To date, the use of solely MSWI fly ash into polymer composites has not been reported because it contains more harmful toxic metals, which can be released into the environment through weathering and leaching (Lam et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation